The growth-employment-poverty nexus in Latin America in the 2000s: Brazil country study - Guillermo Cruces; Gary Fields; David Jaume; Mariana Viollaz (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
During the 2000s, Brazil experienced slow economic growth and a substantial improvement in labour market indicators. From 2001 to 2012, Brazil grew less than the Latin American average. However, the unemployment rate decreased, the employment composition improved, the educational level of workers rose, the share of registered workers increased, and average labour earnings went up. At the same time, poverty and inequality largely diminished. The international economic crisis had a mild effect on the Brazilian economy and some labour market indicators, but the negative effects had been reversed by 2011.
Keywords: O15; J01; J30; 330; Brazil; Latin America; inclusive growth; labour market; poverty